Construção de um algoritmo de orientação para o manejo da pré-eclâmpsia na atenção primária à saúde - Alves, Cindy Souza (2024)
INTRODUCTION: Pre-eclampsia is one of the classifications of Pregnancy-Specific Hypertensive Syndrome characterized by increased blood pressure, accompanied by proteinuria from the 20th gestational week onwards, in addition to being the first cause of maternal death in Brazil during this period. Algorithms are simple, direct and easily accessible instruments, in addition to being essential for quality management in the healthcare field, as a necessary method for organizing processes. OBJECTIVE: Is to build a guidance algorithm for the management of pre-eclampsia in Primary Health Care. This is a methodological study with a mixed approach that was carried out in two stages: survey of existing knowledge about pre-eclampsia through a scope review; construction of an educational learning algorithm based on the survey carried out in the previous stage. METHOD: The work was developed in accordance with the recommendations of the Joanna Briggs Institute for Scoping Review and the PRISMA-ScR Checklist. The selection of studies included two reviewers working independently using the Rayyan-Intelligent Systematic Review management software. The following electronic databases were used: Medline via PubMed, VHL, Embase, Scopus. For gray literature, we searched the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel as a way of standardizing collection in these databases. A total of 696 articles were identified, through screening and removal of duplicates, only 18 articles were selected for study, with an unlimited time frame. To construct the algorithm, the content was based on the regulations of the High-Risk Pregnancy Manual 2023 and the Brazilian Federation of Gynecology and Obstetrics Associations. RESULTS: Of the selected studies, ten highlighted the weaknesses of health professionals regarding the definition of pre-eclampsia, its possible complications and how to refer these pregnant women due to suspicion of the pathology. The construction of new protocols, educational technologies such as flowcharts and algorithms and programs for early detection of pathology are important strategies for reducing rates. The development of the algorithm aims to stimulate and awaken in nurses the importance of effective and efficient monitoring through nursing consultations, especially with regard to early detection and management of pre-eclampsia in Primary Health Care. CONCLUSION: The results obtained in the scoping review offer relevant information for the assistance to pregnant women and the qualification of professionals, highlighting the need to implement educational actions and interventions with a view to managing pre-eclampsia and defining behaviors that are effective for improving care. professionals working in PHC, but for this to happen, it is also necessary to restore the UBS as the main point for better monitoring and detection of pathology, facilitating access to health units, guaranteeing a structure suitable for care needs, avoiding the fragmentation of services.